Kohesi pada Novel Cinta Suci Zahrana Karya Habiburahman El Shirazy - Ira Yuniati; Chairunnisa Chairunnisa (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
This study aims to determine the cohesion marker used in the Cinta Suci Zahrana novel especially in the last chapter titled Cinta Suci Zahrana. This research uses qualitative research method with content analysis technique. The data in this research is cohesion in Novel Cinta Suci Zahrana by Habiburrahman El Shirazy. The source of data is the novel of Cinta Suci Zahrana by Habiburrahman El Shirazy. The data on the cohesion in the novel of the Cinta Suci Zahrana by Habiburrahman El Shirazy is analyzed by steps in tracking the relationship of every two sentences in pairs, ie the relationship between a sentence with a preceding sentence characterized by the use of the cohesion marker. The results of research based on cohesion mechanisms between the sentences contained in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy there is a grammatical cohesion which includes referring, replacing, and sequencing. In addition, lexical cohesion is used which includes repetition, antonymy, collocation, hyponimi, and equivalence. Keywords: Cohesion, Novels, Discourse Analysis